Penggunaan Metode Make a Mach dalam Peningkatan Hasil Belajar Al-Qur’an Hadis pada Siswa Kelas VIII MTsN 9 Aceh Utara - Mursyidah, Mursyidah (Ahdāf: Jurnal Pendidikan Agama Islam, 2023)
The learning outcomes in Al-Qur'an Hadith lessons in this study are changes in the ability and behavior of class VIII MTsN 9 Aceh Utara using the Make a Match method in learning. This study aims to: 1) find out how far the learning outcomes of the Qur'an Hadith have increased in class VIII students of MTSN 9 Aceh Utara for the 2021/2022 academic year using the Make a Match method, and to find out the obstacles faced by teachers in using this method. The approach used in this qualitative research is Classroom Action Research (CAR). The samples taken were 25 students, while the data were obtained by observation, interviews, and questionnaires. The results showed that the Make a Macht method was effectively used in improving student learning outcomes at MTSN 9 Aceh Utara. This was evidenced by an increase in students' learning interest in doing assignments, a willingness to ask questions and express opinions. Through a comparison of student test results between cycle I and cycle II it was found that, in the test results of cycle I, only 13 (53%) students were complete in learning. After the second cycle was carried out, the student test results experienced an increase where as many as 24 students (96%) completed the lesson. The increase in student learning outcomes occurs gradually from the category of incomplete and finally complete (from low to high). It was concluded that in improving learning outcomes of Al-Qur'an Hadith in class VIII MTsN 9 students can apply the make a match method.